Karakteristk Perkembangan Anak Usia Sekolah TK (0-5) Tahun - Ramadan Lubis; Tri Fauziah Hasana; Putri Hasanah Hrp; Iga Nailah Aulia Br Lubis; Amalia Alfina Siagian; Yesa Dwi Khairani; Muhammad Edi Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
At the age of 0-5 years, it is a very important period in the development of a child. At this time, the development process takes place quickly. At this time, it is a sensitive period, because during this time children are especially easy to receive stimuli from their environment. At this time, children are ready to do various activities to better understand and master their environment, which is also a golden age. The golden age where children begin to be sensitive to receive various stimulations and various educational efforts from their environment, both intentional and unintentional. The purpose of this research is to find out the characteristics of spiritual development in children aged 0-5 years. This research discusses how physical development, intellectual development, emotional development, social and moral development in children. This research uses a literature study method (library research) which involves explanations from books, journals that are relevant to the object of study.